The synthesis diagnostic test systems on the basis of polymer microspheres in the presence of polyvinylpyrrolidone modified with an amino acid - Z. B. Artykova; I. A. Gritskova; S. A. Gusev; L. Y. Basyreva; V. A. Sotchilin; M. I. Shtilman; A. V. Goryachaya; G. P. Kheynman; S. A. Kedik; N. I. Prokopov (Тонкие химические технологии)
Styrene-divinylbenzene particles (6 microns in diameter) with carboxyl groups on the surface have been synthesized by seed polymerization in the presence of an organosilicon carboxyl-containing surfactant soluble in the monomer phase. It has been shown that carboxyl groups on the microsphere surface are accessible for covalent immobilization of bioligands and alanine-modified polyvinylpyrrolidone. It was supposed that applying modified polyvinylpyrrolidone for obtaining diagnostic systems based on polymer microspheres is very perspective.